DAMPAK KEBISINGAN TERHADAP FUNGSI PENDENGARAN DAN TEKANAN DARAH PADA PEKERJA TYRE DI WORKSHOP PT. RAHMAN ABDIJAYA DI KABUPATEN TABALONG - Wenny Wulandani; Salamiah Salamiah; Akhmad Rizali; Eko Suhartono (EnviroScienteae, 2015)
Mechanism process and work activity  tyre unit in PT. Rahman Abdijaya workshop using machines and working equipments. Noise with high intensity of those machines and working equipments will raise noise exposure and will increase the risk of the worker.  This study aims to analysis affect of noise to hearing function and blood pressure at tyre worker in workshop PT. Rahman Abdijaya   in  Tabalong district.  It is an observational study with cross-sectional design. Sample size was 32 worker. Data collection by audiometric  measurement, tension before and after working measurement also noise in working environment measurement. Univariat analysis, bivariat analysis. With chi-square test are used to analyzed the data. The results of the study showed that there was not significant affect of noise to hearing function (sig.α = 0,401 > 0,05), but there was significant affect of noise to sistole blood pressure (sig.α = 0,039 < 0,05) and diastole blood pressure (sig.α = 0,019 < 0,05). Suggestion for the company are necessary noise measurement in all working company area, maintenance activity must be done for periodically and all of broken equipment must be replaced, audiometric measurement every ones in a year, blood pressure measurement must be controlled, Safety sign compatible as safety and health risk, prepared APD like ear muff, training  and socialized about noise affect to the health and how to control them.